Research trends in nutritional interventions for stroke: a bibliometric analysis and literature review - Xie, Yipeng; Xiong, Yuan; Sun, Mengyue; Zhao, Yan; Wu, Miao (Frontiers in Nutrition, 2024)
Background: Over the past 23 years, there has been a thorough analysis of literature concerning nutritional interventions, nutrients, and feeding approaches related to stroke. Furthermore, a scientific knowledge map was established, elucidating the current state of research, examining its development and trends, and offering new research viewpoints for the future.This study aimed to investigate global and emerging research trends in nutritional interventions for stroke from 2000 to 2023 through bibliometric analysis. Methods: A bibliometric analysis of literature from the Core Collection of Scientific Networks for the years 2000-2022 was conducted. CiteSpace, VOSviewer, and bibliometric graphical software were used to identify major contributors to publications, including authors, countries, institutions, journals, references, and keywords.Results ： The bibliometric analysis yielded a total of 464 publications. This is a gradually increasing number in terms of the number of publications during the study period. China had the highest number of publications. Clinical Nutrition" was the journal with the highest number of relevant publications, and the most commonly used keywords were "stroke", "nutrition" and "malnutrition".: These analyses reveal research trends in nutritional therapy for stroke from 2000 to 2023 and point to prospective research frontiers. This study provides a deeper understanding of what nutritional treatment of stroke entails and provides guidance and support for future research in this area.